2016
DOI: 10.1111/1365-2478.12424
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of borehole ambient noise interferometry for permanent reservoir monitoring

Abstract: The analysis of seismic ambient noise acquired during temporary or permanent microseismic monitoring campaigns (e.g., improved/enhanced oil recovery monitoring, surveillance of induced seismicity) is potentially well suited for time‐lapse studies based on seismic interferometry. No additional data acquisition required, ambient noise processing can be automatized to a high degree, and seismic interferometry is very sensitive to small medium changes. Thus there is an opportunity for detection and monitoring of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 44 publications
(88 reference statements)
0
20
0
Order By: Relevance
“…Body waves caused by surface noise sources are also more likely to be detected in boreholes (Behm, 2017;Zhuo and Paulssen, 15 2017) or inside mines (Olivier et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Body waves caused by surface noise sources are also more likely to be detected in boreholes (Behm, 2017;Zhuo and Paulssen, 15 2017) or inside mines (Olivier et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the fluctuations are due to variations in anthropogenic noise. Previous studies by Grechka and Zhao (), Vaezi and Van der Baan () and Behm () have shown that surface activity can indeed be the dominant noise source up to 2 km depth. Our results confirm their observation, extending it to a depth of 3 km.…”
Section: Discussionmentioning
confidence: 90%
“…We did not succeed to identify temporal variations of the medium within the 33 day time span because the cross correlations appeared to be dominated by fluctuations in anthropogenic noise (Figures and S4 in the supporting information). Nevertheless, it should be possible to identify temporal medium variations at locations with more stable noise environments, as shown by Behm ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…anisotropy, sets of directional discontinuities; Di Giulio et al, 2009) and their changes with time (e.g. shear wave velocity decrease due to crack opening or water level rise; Daskalakis et al, 2016;Behm, 2016), potentially providing an indirect assessment of strength degradation or stress changes. Furthermore, monitoring of acoustic emissions, i.e.…”
Section: Open Discussion: the Lesson Of A Killer Landslidementioning
confidence: 99%